Pelatihan Pembuatan Jeli dan Permen Jeli Bunga Telang Bagi Komisi Wanita GBI Kalijaya, Tangerang - Mastuti, Titri Siratantri; Handayani, Ratna; M. Siregar, Tagor; Cornelia, Melanie; R. Pokatong, W.Donald; Kurniawan, Reynaldi; M. N. Sanaky, Florecita (Program Studi Teknik Industri, Fakultas Teknik, Universitas Katolik Indonesia Atma Jaya Jakarta, 2024)
Telang flowers or Butterfly Pea is often found or planted independently by people, one of which is in the Kalijaya area, Tangerang. As public knowledge and awareness of health increases, Telang flowers are widely consumed conventionally as a tea brew because it is known for the high antioxidant content of telang flowers. One of activity and service of the women'scommission at GBI Kalijaya Tangerang is to increase the creativity of its congregation so that it can improve welfare through improving its economy. Jellies and jelly candies are loved by all groups, both young and old and are easy to make. The UPH Food Technology Study Program was moved to help provide training through Community Service activities. Butterfly pea flowers can be used as a source of coloring in jelly to increase its appeal. Training activities were carried out in two parts, first, explanation regarding the technology for making jelly and jelly candy and knowledge of anthocyanin compounds in butterfly pea flowers as antioxidants. The second is the practice of making jellies and jelly candies. The results of the training can be understood by participants, where they are motivated to practice at home and intend to pass on the information to others.